Influence of carbon nanotube length on toxicity to zebrafish embryos - Cheng J (Dove Medical Press, 2012)
Jinping Cheng,1,2 Shuk Han Cheng11Department of Biology and Chemistry, City University of Hong Kong, Hong Kong; 2State Key Laboratory of Estuarine and Coastal Research, East China Normal University, Shanghai, ChinaAbstract: There is currently a large difference of opinion in nanotoxicology studies of nanomaterials. There is concern about why some studies have indicated that there is strong toxicity, while others have not. In this study, the length of carbon nanotubes greatly affected their toxicity in zebrafish embryos. Multiwalled carbon nanotubes (MWCNTs) were sonicated in a nitric acid solution for 24 hours and 48 hours. The modified MWCNTs were tested in early developing zebrafish embryo. MWCNTs prepared with the longer sonication time resulted in severe developmental toxicity; however, the shorter sonication time did not induce any obvious toxicity in the tested developing zebrafish embryos. The cellular and molecular changes of the affected zebrafish embryos were studied and the observed phenotypes scored. This study suggests that length plays an important role in the in vivo toxicity of functionalized CNTs. This study will help in furthering the understanding on current differences in toxicity studies of nanomaterials.Keywords: length, carbon nanotubes, sonication, developmental toxicity, zebrafish